Pegylation of poly([gamma]-benzyl-L-glutamate) nanoparticles is efficient for avoiding mononuclear phagocyte system capture in rats (2010)
ABSTRACT: Poly(γ-benzyl-L-glutamate) (PBLG) derivatives are synthetic polypeptides for preparing nanoparticles with well controlled surface properties. The aim of this paper was to investigate the biodistribution of pegylated PBLG in rats. For this purpose, nanoparticles were prepared by a nanoprecipitation method using mixtures of different PBLG derivates, including a pegylated derivate to avoid mononuclear phagocyte system uptake. The morphology, size distribution, and surface charge of the nanoparticles were investigated as a function of the amount of polymer employed for the preparation. Moderately polydispersed nanoparticles (polydispersity index less than 0.2) were obtained. Their size increased with polymer concentration. The zeta potential values were negative whatever the formulations. The availability of polyethylene glycol chains on the nanoparticles’ surface was confirmed by measuring the decrease in bovine serum albumin adsorption. For in vivo distribution studies, pegylated and nonpegylated nanoparticles were prepared with polymer mixtures containing PBLG-fluorescein isothiocyanate and imaged by fluorescence microscopy to measure their accumulation in liver and spleen tissues of rats after intravenous administration. Injection of stealth formulations resulted in negligible fluorescence in liver and spleen compared with nonpegylated formulations, which suggests that these nanoparticles are promising candidates as a stealth-type long-circulating drug carrier system and could be useful for active targeting of drugs while reducing systemic side effects.